Clyde Street 1833-1841: The veterinary teaching and learning environment - Macdonald, Alastair A (Veterinary History Society, 2020)
The teaching environment of the veterinary school in Clyde Street, Edinburgh, in the 1830s, comprised many different components for each of the students who attended. It is obviously not possible to describe them all, but important to attempt to give something of an impression as this is missing from the current literature.
Keywords: Veterinary History